Transfer of affective connotations in the basic lexicon of Spanish learners of L2 English - Ana Blanco Canales; Elisa Pérez-García (Revista de Lingüística y Lenguas Aplicadas)
This study addresses emotion in second languages with the aim of understanding how late bilinguals incorporate the affective connotations of core vocabulary into their mental lexicon. Specifically, it examines whether there are emotionality differences between the L2 and the native languages of reference, and whether linguistic competence, contact with the L2 and its culture, and attitudes explain the different tendencies. For this purpose, a group of Spanish learners of L2 English assessed a corpus of 300 words on the affective dimensions of valence and arousal. Different statistical analyses showed that English learners value the lexical repertoire in a very similar way to Spanish speakers, differing markedly from English speakers. It is mainly concluded that the mother tongue exerts a significant influence on this perceptual process and that the emotional connotations of the L2 are incorporated into the mental lexicon through translations from the L1 as a result of an emotional transfer.